Anglo-American legal positivism: Stages of formation and development - Maxim D. Gorbunov (RUDN Journal of Law)
Anglo-American legal positivism is an influential trend in modern legal thought. Understanding this framework is crucial not only for addressing gaps in scientific knowledge within political and legal doctrines but also for applying relevant developments to domestic legal science. This understanding is particularly valuable because it relates to the dominant doctrine of legal positivism in contemporary Russia while also being rooted in an alternative legal paradigm. The purpose of the article is to examine the formation and development of Anglo-American legal positivism as a key area of legal understanding in the world legal scholarship. The author highlights the characteristics of Anglo-American positivism, its main developmental stages, and the ideas of its leading representatives. Methodologically, this study employs a combination of philosophical, general, and special scientific methods, including dialectical and historical approaches, general logical techniques, and comparative analysis. Specific methods of analytical philosophy are also used, including methods of contextual and conceptual analysis. The study concludes that Anglo-American legal positivism has evolved through three stages: the classical stage associated with command theory; the neopositivist stage, where new analytical and philosophical approaches emerged; and the modern stage, characterized by debates between "inclusive" and "exclusive" positivism.